2018
DOI: 10.1099/ijsem.0.002828
|View full text |Cite
|
Sign up to set email alerts
|

Blastococcus atacamensis sp. nov., a novel strain adapted to life in the Yungay core region of the Atacama Desert

Abstract: A polyphasic study was undertaken to establish the taxonomic status of a Blastococcus strain isolated from an extreme hyper-arid Atacama Desert soil. The isolate, strain P6, was found to have chemotaxonomic and morphological properties consistent with its classification in the genus Blastococcus. It was shown to form a well-supported branch in the Blastococcus 16S rRNA gene tree together with the type strains of Blastococcus capsensis and Blastococcus saxobsidens and was distinguished from the latter, its clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 76 publications
1
21
0
1
Order By: Relevance
“…Members of the family Geodermatophilaceae have received the most attention, notably the genera Blastococcus, Geodermatophilus and Modestobacter ; members of these taxa are known to be resistant to desiccation, ionizing radiation, UV‐light and heavy metals (Sghaier et al ). Dereplicated Geodermatophilaceae strains from Atacama Desert habitats have been validly named as Blastococcus atacamensis (Castro et al ), Geodermatophilus chilensis (Castro et al ) and Modestobacter caceresii (Busarakam et al ) and shown to have moderately large genomes (3·9–5·9 Mb). Representatives of these taxa not only contain NP‐BGCs but also stress‐related genes that encode for properties such as carbon starvation, temperature fluxes, osmotic stress and UV‐light.…”
Section: Desertsmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the family Geodermatophilaceae have received the most attention, notably the genera Blastococcus, Geodermatophilus and Modestobacter ; members of these taxa are known to be resistant to desiccation, ionizing radiation, UV‐light and heavy metals (Sghaier et al ). Dereplicated Geodermatophilaceae strains from Atacama Desert habitats have been validly named as Blastococcus atacamensis (Castro et al ), Geodermatophilus chilensis (Castro et al ) and Modestobacter caceresii (Busarakam et al ) and shown to have moderately large genomes (3·9–5·9 Mb). Representatives of these taxa not only contain NP‐BGCs but also stress‐related genes that encode for properties such as carbon starvation, temperature fluxes, osmotic stress and UV‐light.…”
Section: Desertsmentioning
confidence: 99%
“…Another important development is the realization that in some actinobacterial taxa, such as the genera Amycolatopsis , Frankia and Micromonospora , there is a link between the distribution of NP‐BGCs and phylogeny (Adamek et al ; Carro et al ; Nouioui et al ). In addition, information drawn from whole‐genome sequences is providing fascinating insights into how micro‐organisms adapt to extreme habitats, as witnessed by the ability of members of the actinobacterial family Geodermatophilaceae to withstand extreme environmental conditions that prevail in hyperarid desert habitats (Castro et al , b).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, many of the stress related genes were shown to be linked with carbon starvation, oxidative and osmotic stress, resistance to UV radiation and temperature fluxes, as exemplified by genes encoding for carbon starvation protein A (CstA), which promotes peptide uptake [72][73][74]; sox genes associated with responses to oxidative stress [75,76]; KatE and uvrD genes linked to protection against reactive oxygen and UV-radiation [77]; dnaK and dnaJ, hrcA, grpE and Hsp genes related to responses to heat shock [78]; a family of proteins associated with cold shock responses [79] and coxE, coxD and coxG genes along with a coxSML cluster coding for utilisation of carbon monoxide indicating that the isolate may have a chemolithoautotrophic lifestyle [80]. Similar patterns of stress-related genes have been detected in the genomes of the type strains of the B. atacamensis [16], G. chilensis [17], M. caceresii [10] and 'M. excelsi' [3].…”
mentioning
confidence: 60%
“…excelsi' are rich in stress genes that provide an insight into how these organisms have adapted to the prevailing environmental conditions in hyper-arid Atacama Desert soils [3,10]. Moreover, genomes of representative type strains of the family Geodermatophilaceae revealed many biosynthetic gene clusters (BGCs) related to the biosynthesis of secondary metabolites, as exemplified by the genomes of the type strains of Blastococcus atacamensis [16], Geodermatophilus chilensis [17], M. caceresii [10] and 'M. excelsi' [3].…”
mentioning
confidence: 99%
“…This genus was dominant in the SW control, whereas the contribution of Blastococcus was drastically lower. Blastococcus strains have been reported as adapting to drought conditions [33]. Touceda-González et al [34] reported a high abundance of Blastococcus genera in the rhizosphere of Alyssum serpyllifolium-nickel hyperaccumulating plant species growing in ultramafic soils.…”
Section: Plant Driven Changes In Functional and Genetic Diversity Of mentioning
confidence: 99%